Banana (Musa acuminata), orange (Citrus reticulata), and watermelon (Citrullus lanatus) peels as prebiotic - Abdul Rahim, Erra Fazira; Sui, Sien Leong; Sarbini, Shahrul Razid; Latif, Kamil; Malahubban, Masnindah (UNIMAS Publisher, 2022)
Fruit waste is being studied as a non-conventional alternative source of nutritional and mineral content that might be employed as functional food ingredients. This study aims to identify the 1) proximate and mineral composition of banana, orange and watermelon waste powder subjected to different drying methods; 2) prebiotic potential of the fruit waste powder (FWP) in growth enhancement of the probiotic Lactobacillus casei. The fruit peels were processed by two methods: freeze-dried and oven-dried. All FWP was sterilised and milled into particle size <180μm. The proximate (total ash, crude protein, crude fat, crude fibre), mineral (Ca, Zn, Na, K, Mg, Cu) profiling was analysed in triplicate according to standard. Prebiotic activities of FWP were determined through the growth of L. casei analysed. Significant differences (p<0.05) result was observed between the proximate and mineral parameters in all FWP. Watermelon FWP had the highest moisture, ash, sodium, potassium, phosphorus, and zinc content, while banana FWP contained the highest crude protein, crude fat, and magnesium content. Both banana and watermelon FWP were found to exhibit high crude fibre content. The orange WP was reported with the highest carbohydrate, calcium, and copper content. Although significant differences (p<0.05) in composition were noted, the oven and freeze-drying methods employed showed no pronounced effect. Calcium, copper content (all FWP), sodium and phosphorus (watermelon FWP), phosphorus (banana FWP) examined highly exceeded the recommended dietary allowance (RDA) limit. Banana FWP showed the highest L. casei net growth of log10 8.28±0.02– 8.36±0.01 CFU/mL and 91.61–98.66% of survival rate, thus showing its potential as prebiotic agents among other FWP. All types of FWP showed significant difference (p<0.05) in bacterial growth except for oven-dried orange FWP. Overall, the results revealed that all these fruit wastes could be exploited for the nutrient and value-added potential in food formulations due to their inexpensiveness, natural, safe, and environmental friendliness.